2016
DOI: 10.1038/leu.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of three low-dose intensity subcutaneous bortezomib regimens in elderly frail patients with untreated multiple myeloma

Abstract: 54This phase 2 trial evaluated 3 low-dose intensity subcutaneous bortezomib-based treatments in 55 patients ≥75 years with newly diagnosed multiple myeloma (MM). Patients received subcutaneous 56 bortezomib plus oral prednisone (VP, N=51) or VP plus cyclophosphamide (VCP, N=51) or VP plus 57 melphalan (VMP, N=50), followed by bortezomib maintenance, and half of the patients were frail. 58Response rate was 64% with VP, 67% with VCP and 86% with VMP, very good partial response 59 rate or better was 26%, 28.5% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Two prospective randomized studies in elderly frail myeloma patients have also shown that adding either cyclophosphamide or melphalan or thalidomide to bortezomib and dexamethasone does not offer significant benefit in terms of response rates and progression-free survival, although it increases toxicity. 13, 14 Triple combinations are considered the standard for induction in younger, transplant eligible myeloma patients, 22 but our data and the data from elderly frail myeloma patients show that it is difficult to extrapolate the results from studies in fitter patients and apply them in frail patients, such as those with AL amyloidosis.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Two prospective randomized studies in elderly frail myeloma patients have also shown that adding either cyclophosphamide or melphalan or thalidomide to bortezomib and dexamethasone does not offer significant benefit in terms of response rates and progression-free survival, although it increases toxicity. 13, 14 Triple combinations are considered the standard for induction in younger, transplant eligible myeloma patients, 22 but our data and the data from elderly frail myeloma patients show that it is difficult to extrapolate the results from studies in fitter patients and apply them in frail patients, such as those with AL amyloidosis.…”
Section: Discussionmentioning
confidence: 84%
“…13, 14 For patients with AL amyloidosis, the combination of VCD is considered as a ‘standard’ regimen for primary therapy in most centers, 1, 15, 16 but it is not clear whether the addition of a third drug (cyclophosphamide) to the bortezomib/dexamethasone (VD) backbone further and significantly improves efficacy, given the substantial activity of bortezomib itself. Also, it is not clear whether cyclophosphamide is the optimal partner of VD, among other potential partners, including other alkylating agents.…”
Section: Introductionmentioning
confidence: 99%
“…Two prospective randomized studies in elderly frail myeloma patients have also shown that adding either cyclophosphamide or melphalan or thalidomide to bortezomib and dexamethasone does not offer significant benefit in terms of response rates and progression-free survival, although it increases toxicity. 13,14 Triple combinations are considered the standard for induction in younger, transplant eligible myeloma patients, 22 but our data and the data from elderly frail myeloma Figure 1. OS of patients treated with VD or VCD (all patients).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 For patients with AL amyloidosis, the combination of VCD is considered as a 'standard' regimen for primary therapy in most centers, 1,15,16 but it is not clear whether the addition of a third drug (cyclophosphamide) to the bortezomib/dexamethasone (VD) backbone further and significantly improves efficacy, given the substantial activity of bortezomib itself. Also, it is not clear whether cyclophosphamide is the optimal partner of VD, among other potential partners, including other alkylating agents.…”
Section: Introductionmentioning
confidence: 99%
“…[57][58][59] But in frail elderly patients, the benefit of triplets is less evident because they may be more toxic, particularly with regard to hematologic toxicity. [89][90][91] Therapeutic strategies should be defined after careful assessment of the frailty profile. Doses and mode of administration should be adapted.…”
Section: Case Studiesmentioning
confidence: 99%